Petal of Resistance: Language as a Backbone of Identity Reconstruction in Naipaul’s The Mimic Men - Benabida, Salima; Kerboua, Salim (LANGUAGE ART, 2022)
This paper tends to examine resistance through narratives in the postcolonial context. It focuses on the postcolonial counter-discourse in Naipaul’s novel, The Mimic Men (1967), through the analysis of Ralph Singh’s, use of the English language as a subversive tool by which he attempts to reconstruct his identity. This research presents an analytical framework for analyzing the novel’s discourse, which concentrates on the writer’s narrative tactics and use of language, abrogation and appropriation, to oppose the prevailing culture. However, in the postcolonial era, a distinct discourse emerged through scholarly panel discussions like Ngugi’s, Hall’s, Fanon's and Bhabha's concepts about language, culture and the oppressed people’s psyche along with some defensive mechanisms such as mimicry and hybridity, which, in return, theorized resistance and identity reconstruction through language. Thus, this study will critically explore the exiled subjects’ resistance rhetoric in order to determine the migrants’ existence and identity reconstruction in the Western sphere through an examination of the use of mimicry and hybridity in the novel. Although the novel is mostly written in English, the use of some exospheric references give it sense of nativism and make it as a sarcastic postcolonial narrative that criticizes the colonial hegemony and sheds light on the dilemma of the colonized individual’s psychological melancholy.